Tips for 6 Months After COVID-19 Pneumonia: Acute Inflammatory Parameters - Engin Aynacı; Gökhan Karakurt (Bagcilar Medical Bulletin, 2023)

(untitled)
Objective:In our study, we aimed to investigate the long-term effects of the acute phase parameters of C-reactive protein, procalcitonin, D-dimer, lymphocyte, thrombocyte and ferritin on the respiratory function parameters in patients hospitalized due to Coronavirus disease-2019 (COVID-19) pneumonia.Method:The present study was carried out with the retrospective evaluation of patients with COVID-19 pneumonia, who were hospitalized in Medipol University Hospital between March 2020 and June 2021, and who were 6 months to 1 year after discharge. The relationship between pulmonary function test results and acute period laboratory findings of 52 patients who applied for control purposes 6 months after discharge was examined.Results:Diffusing capacity for carbon monoxide (DLCO) (pred) value in 26 patients (50%), total lung capacity (TLC) value in 9 patients (17.3%), and residual volume (RV) (pred) value in 10 patients (19.2%) were below 80%. As a result of multiple linear regression analysis in our study, the maximum D-dimer level and maximum procalcitonin level were determined by DLCO (% pred) (adjusted R2 =0.645; p<0.001), TLC (% pred) (adjusted R2 =0.582; p=0.003) and RV (% pred) (adjusted R2 =0.560; p=0.001) values and were independent determinants in predicting these values.Conclusion:High D-dimer and procalcitonin levels in the acute period in patients with COVID-19 pneumonia may predict losses in respiratory function parameters such as DLCO, TLC, RV in the longer term than 6 months. Long-term follow-up of these patients is important in terms of respiratory function.